2015
DOI: 10.1021/acs.iecr.5b03366
|View full text |Cite
|
Sign up to set email alerts
|

Capillary Dynamics of Water/Ethanol Mixtures

Abstract: Surface tension and contact angle play important roles in capillary dynamics during washing commission of spray-dried detergent powder where interaction between surface chemistry and liquid is concerned. An experimental study for the dynamics of water/ethanol mixtures in both hydrophilic and hydrophobic capillary tubes has been investigated. The combination of water/ethanol mixtures and Trimethylchlorosilane coating on capillaries provides a variety of liquid surface tension and contact angle for the penetrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 42 publications
6
20
0
Order By: Relevance
“…Measuring contact angle on rough surfaces, such as those formed for a bed of microsized fibers, can be challenging since the observed angle is the manifestation not just of the molecular interactions at the solid/liquid interphase but also of the microstructure of the surface (Figure 3). This effect is counted by the model of Wenzel which predicts that if a molecularly hydrophobic surface is rough, the appearance is that of an even more hydrophobic surface [27,28]. An interesting evidence of this phenomenon in particulate fibers is shown in Figure 4, where the contact angle of several groups of sugarcane bagasse fibers treated with solutions of variable silane concentrations appears almost invariant (between 122° and 129°), even though the absorbed amount of silane changes nearly in one order of magnitude (5.5 × 10 −5 to 1.04 × 10 −4 mol of silane per gram of fiber).…”
Section: Preparation Of Bagasse Microfibers For Biocomposite Fabricationmentioning
confidence: 99%
“…Measuring contact angle on rough surfaces, such as those formed for a bed of microsized fibers, can be challenging since the observed angle is the manifestation not just of the molecular interactions at the solid/liquid interphase but also of the microstructure of the surface (Figure 3). This effect is counted by the model of Wenzel which predicts that if a molecularly hydrophobic surface is rough, the appearance is that of an even more hydrophobic surface [27,28]. An interesting evidence of this phenomenon in particulate fibers is shown in Figure 4, where the contact angle of several groups of sugarcane bagasse fibers treated with solutions of variable silane concentrations appears almost invariant (between 122° and 129°), even though the absorbed amount of silane changes nearly in one order of magnitude (5.5 × 10 −5 to 1.04 × 10 −4 mol of silane per gram of fiber).…”
Section: Preparation Of Bagasse Microfibers For Biocomposite Fabricationmentioning
confidence: 99%
“…Cao et al [13] investigated the dynamics of water/ethanol mixtures in capillary tubes and found that surface tension plays an important role in the travelling speed inside the capillary tubes. O'Loughlin et al [14] investigated the capillary rise dynamics of glycerol and aqueous glycerol solutions in vertical glass capillaries of various radii.…”
Section: Introductionmentioning
confidence: 99%
“…We further examined whether the capillary rise dynamics can be attributed to ethanol, oleic acid, or their mixture by repeating the capillary rise experiment in a tube coated with pure ethanol (Figure 2c). Being soluble in water and affecting the surface tension and viscosity of the water‐ethanol mixture (Cao et al, 2015), the capillary rise of water in the ethanol‐coated tube was substantially lower than that of water in the uncoated tube (Figure 2a vs. Figure 2c).…”
Section: Model Validation By Experimental Studies For Uniform Capillamentioning
confidence: 99%